Overview of the Irish brewing and distilling sector: processing inputs supply and quality requirements - Umego, Ekene C.; Barry-Ryan, Catherine (BrewingScience, 2022)
For any brewing and distilling establishment, the supply and quality of processing inputs is a major determinant in its production output. Accessibility and availability of brewing and distilling inputs drives productivity and quality of products. The Irish brewing and distilling sector have shown increased sales and production output, with a growth rate of 4% between 2014 and 2019. The brewing industry in the republic of Ireland has seen a 22% increase in the number of micro-breweries since 2014, and its total output now stands at 8.3 m hectolitres. The distilling industry witnessed an increase from four to thirty-eight in the number of distilleries between 2010 and 2020 with a local and global sales at 2.4 and 20 million nine litre cases, respectively. As a result of the continued growth of the Irish brewing and distilling sector, demand for different processing inputs has increased proportionately. For a sustainable production process, there is need for a steady supply of the right quantity and quality of the major inputs for brewing and distilling. Sustainable growth of the sector requires establishment of a strong base of processing inputs availability and their effective utilisation to minimise environmental impacts. This review, therefore, looks at the current state of the major processing inputs for brewing and distilling in Ireland, as well as their general characteristics and requirements.